Stakeholder’s engagement process regarded the issues arose between CIMB Malaysia and customer - Nurul Saadah, Md Isa (Universiti Malaysia Sarawak (UNIMAS), 2014)
This research is all about stakeholder engagement that happens between CIMB organization and customers. Researcher identifies main problem and separate into other problem because of the main problem. Stakeholder engagement is want to identify either this organization deal with the customer's problem or not. For data collection, this research use social media Facebook comment as data. Official CIMB's Facebook is identify and data collection start since problem is detect until problem is solve and the issues never be stated again by customers. Finding found out that CIMB gave superficially addressing the stakeholder's voice when they served their customer. With manner and courtesy they reply the comment hope that their customer will understand. Recommendation for this research hope that time to collect data is added and also used another social media to multiple data collection.